Evaluation of Forensic Autopsy Cases Performed in 2004 in İzmir - Çengel, Gülden; Ergönen, Akça Toprak; Can, İsmail Özgür; Sönmez, Yonca (The Bulletin of Legal Medicine, 2008)
Various investigations were aimed to highlight the findings related to the cause, manner and mechanism of deaths for medicolegal purposes. A few and limited studies were performed related to this issues in our region.In our study, we aimed to research medicolegal deaths with regard to age, gender, place of death, manner and cause of death and toxicological investigations.Autopsy reports of 1051 cases were evaluated according to determined parameters retrospectively at Council of Forensic Medicine, Izmir Group Chairmanship Morgue Branchin the year 2004.The mean age was 40.12 + 19.55 and 79.5 % of the cases were male. In the majority of the cases the manner of death was found natural. Cardiovascular system disease, cancer and infections were the leading cause of death (35.1%), other cause of death were listed as follows; 18.5 mechanic asphyxia, 17.2% firearm wounds, 9.8% stab wounds. Natural deaths in children and women were significantly higher than in adults and men in order. Most of the asphyxial deaths occurred among children and women.In conclusion, our findings showed age groups, gender, region and seasons could affect the manner arid cause of deaths and also intoxications.Keywords: Medicolegal autopsy, cause of death, manner of death
Keywords: medicolegal autopsy; cause of death; manner of death